2012
DOI: 10.1016/j.numecd.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic discrepancies in the metabolic syndrome begin in childhood and persist after adjustment for environmental factors

Abstract: Background-Evaluation of metabolic syndrome (MetS) characteristics across an age spectrum from childhood to adulthood has been limited by a lack of consistent MetS criteria for children and adults and by a lack of adjustment for environmental factors. We used the pediatric and adult International Diabetes Federation (IDF) criteria to determine whether gender-and race-specific differences in MetS and its components are present in adolescents as in adults after adjustment for socioeconomic status (SES) and lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
117
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 35 publications
4
117
0
Order By: Relevance
“…[9][10][11][12][13][14] This is a concern because non-Hispanic-black individuals have higher rates of T2DM and CVD despite low rates of ATP-III MetS diagnosis. [15][16][17][18][19] The recently developed MetS Severity Score (MetS z score) calculator addresses the epidemiologic limitations of the ATP-III criteria. 20,21 This tool accounts for differences in MetS by race/ethnicity and gender.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] This is a concern because non-Hispanic-black individuals have higher rates of T2DM and CVD despite low rates of ATP-III MetS diagnosis. [15][16][17][18][19] The recently developed MetS Severity Score (MetS z score) calculator addresses the epidemiologic limitations of the ATP-III criteria. 20,21 This tool accounts for differences in MetS by race/ethnicity and gender.…”
mentioning
confidence: 99%
“…17 However, racial/ethnic discrepancies in MetS may affect its relationship to NAFLD. Non-Hispanic black adolescents have a lower prevalence of MetS [24][25][26][27]18,[28][29][30] despite having more IR. 26,[31][32][33][34][35] Conversely, Hispanics have a higher prevalence of NAFLD despite similar rates of MetS.…”
Section: E718mentioning
confidence: 99%
“…26,[31][32][33][34][35] Conversely, Hispanics have a higher prevalence of NAFLD despite similar rates of MetS. 5,7,13,18,24,25 Given these intergroup differences, our goal was to assess relationships among MetS, IR, and NAFLD between racial/ ethnic groups. We evaluated adolescents from the NHANES for unexplained elevations in ALT as a potential marker for NAFLD.…”
mentioning
confidence: 99%
“…In humans, loss of homeostatic control can lead to toxic levels of blood glucose and the development of obesity and type 2 diabetes, diseases characterized by decreased ability to respond to and metabolize glucose. Twin, family, and epidemiological studies have demonstrated a significant genetic component for diseases of glucose toxicity (reviewed in Vimaleswaran and Loos 2010;Walker et al 2010). Genetic background can be thought of as setting a threshold for glucose toxicity, and environmental factors such as diet and physical activity determine whether an individual crosses that threshold.…”
mentioning
confidence: 99%